Early detection and treatment of schizophrenia: how early? - Riecher-Rössler, A.; Gschwandtner, U.; Borgwardt, S.; Aston, J.; Pflüger, M.; Rössler, W. (Acta psychiatrica Scandinavica, 2006)
Objective:  Whereas early detection and therapy of schizophrenic psychoses until some time ago concentrated on frank schizophrenia, during the last years some centres have also started to treat patients even before a clear diagnosis could be established. This paper attempts to discuss if and when this is justified in the light of recent research. Method:  Mini review of literature. Results:  The rationale for early detection and treatment of schizophrenia is based on several observations: diagnosis and treatment of schizophrenia are often seriously delayed. Consequences of the disease are severe already in the early undiagnosed phase of the disorder and early treatment seems to improve the course of the disease. It can therefore be stated quite safely that patients should be treated as early as possible. However, the question of how early has not been sufficiently answered up to now. Conclusion:  We are at the moment in an ethical dilemma between either diagnosing and treating this disorder too late or too early. The only way and prerequisite for solving this dilemma is a more reliable identification of individuals at risk and the beginning disease process.